Fatigue Crack Propagation in Shot Peened al 7475-t7351 Alloy Specimens - Ferreira, N. (2016)
The approach to engineering design based on the flaws propagation assumption applying the principles of fracture mechanics is commonly used in aluminum structures for aerospace engineering, in which surface shot peening is an attractive method of improving fatigue performance, because it promotes the retardation of the crack initiation and earlier crack growth. The main purpose of present work was to analyze the effect of the surface shot peening on the fatigue crack propagation of the 7475 aluminum alloy with a T7351 heat treatment. Two types of fatigue tests were performed: constant amplitude and variable amplitude loading in which periodic overload blocks of 300 cycles are applied with intervals of Nint cycles. Surface micro shot peened promoted an increasing in micro-hardness only in order or 6% and created negative surface residual stresses in order of -174 MPa, which compare with the positive residual stresses of +291 MPa on the machined specimens. For tests at constant amplitude loading the effect of surface peening on da/dN-ΔK curves is quite limited, particularly for R = 0.4. However, this beneficial effect increases significantly near the threshold. Repeated overload block reduces significantly the fatigue crack propagation rate, being this effect particularly dependent of the intervals between the blocks. The maximum reduction of crack propagation rate and retardation effects were obtained for Nint = 7500 cycles.